Grey social media engagement analysis. Issue 2 (1st August 2016) - Delcea, Camelia
Abstract : Purpose: – Recent studies have shown that customers are more likely to buy a certain product or service from a company they can follow or contact on social media. Moreover, the customers feel a stronger relationship with the companies they are interacting in the virtual networks. But have the companies succeed in getting everything from this strong relationship? Are their online advertising campaigns getting to the right customers? Is there any connection between the social media engagement and the decisions users are taking? This is going to be shaped in this paper through a grey analysis applied to the selected variables. The paper aims to discuss these issues. Design/methodology/approach: – As the nature of the relationships created in the online social networks is characterized by incomplete information, the analysis will make used of the concepts and means offered by the grey systems theory, a theory that have obtained good results over the time when used on uncertain situations. Findings: – By applying a grey relational analysis (GRA) to the considered variables, a strong relationship between the decision easiness and both time spent on social media platforms and number of the accessed websites has been identified. Moreover, it has been determined that the decision happiness is closely related to the companies' websites and their commercials. Research limitations/implications: – The present paper shapes the relationship between the usage of online social media and consumers' decision-making process and decision-making happiness. Due to the fact that the online social media includes billions of users worldwide, the study has some limitations due to the users' number. Originality/value: – The paper uses GRA for drawing the connections between the online social networks reality and its influence to users' every-day life. Considering the present findings, it can be underlined that the identification of the persons which are influential becomes important in order to get to the proper targeted customers.